1998
DOI: 10.1364/ol.23.000846
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the thermal loading of diode-pumped Nd:YVO_4 by use of thermally induced second-harmonic output depolarization

Abstract: A new method of using thermally induced second-harmonic output depolarization to determine the fractional thermal loading of a diode-pumped Nd:YVO(4) laser is proposed. The experimental results show that the fraction of the green output power polarized along the extraordinary axis of a KTP crystal, f(e) , is an oscillatory function of the absorbed pump power. The fractional thermal loading can be determined by measurement of the difference in the absorbed pump power between the peaks of f(e) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…In Nd:YVO , the quantum defect is a fraction 0.24 of the absorbed pump power for the 1064-nm lasing line with a pump source of 808-nm diodes. Previous work [12], [13] has demonstrated that the fractional heat loading can be increased to 0.48 in highly doped material due to other processes [16]. The laser crystals used in the work presented here are all of 0.5% dopant concentration.…”
Section: Theoretical Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…In Nd:YVO , the quantum defect is a fraction 0.24 of the absorbed pump power for the 1064-nm lasing line with a pump source of 808-nm diodes. Previous work [12], [13] has demonstrated that the fractional heat loading can be increased to 0.48 in highly doped material due to other processes [16]. The laser crystals used in the work presented here are all of 0.5% dopant concentration.…”
Section: Theoretical Modelmentioning
confidence: 97%
“…The research work has also been extended to Nd:YVO crystal [12]- [15]. In general, the thermal lensing in Nd:YVO is stronger than that in Nd:YAG.…”
Section: Introductionmentioning
confidence: 99%
“…• C, in order to avoid thermal lens effect [8][9][10]. The polarization match is shown as follows: o(1064 nm) + e(1064 nm) → o(532 nm) for SHG, o(532 nm) + e(1064 nm) → e(355 nm) for THG [11].…”
Section: Methodsmentioning
confidence: 99%
“…The temperature of KTP crystal is required to maintain at a value at which it acts like a QWP for stable operation [4,5]. The optimum temperature was experimentally found to be 24 • C. The temperature was maintained within ±1 • C. To protect the laser head from dust and moisture formation it is placed inside a hermetically sealed cavity which is first evacuated and filled with nitrogen.…”
Section: Description Of the Systemmentioning
confidence: 99%